2013
DOI: 10.1037/a0028339
|View full text |Cite
|
Sign up to set email alerts
|

Smoker reactivity to cues: Effects on craving and on smoking behavior.

Abstract: We assessed craving and smoking in response to smoking-relevant cues. 207 daily smokers viewed images related to one of six cue sets (cigarettes, positive and negative affect, alcohol, smoking prohibitions, and neutral cues) in separate sessions. Compared to neutral cues, cigarette cues significantly increased craving, and positive affect cues significantly decreased craving. When subjects were then allowed to smoke during continuing cue exposure, cues did not affect the likelihood of smoking or the amount smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
97
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 82 publications
14
97
3
Order By: Relevance
“…This has the dual benefit of being parsimonious and also consistent with the data showing that craving intensity is related to outcomes such as smoking and dependence, regardless of source [3,4]. While the proposition that craving intensity matters may seem trivial, we should remember that some authors [5] have suggested that craving is epiphenomenal and perhaps unimportant, so the proposition is not trivial.…”
Section: Cravingsupporting
confidence: 56%
See 1 more Smart Citation
“…This has the dual benefit of being parsimonious and also consistent with the data showing that craving intensity is related to outcomes such as smoking and dependence, regardless of source [3,4]. While the proposition that craving intensity matters may seem trivial, we should remember that some authors [5] have suggested that craving is epiphenomenal and perhaps unimportant, so the proposition is not trivial.…”
Section: Cravingsupporting
confidence: 56%
“…Laboratory assessments cannot capture this. Moreover, the perceived availability of cigarettes is known to modulate craving and response to various laboratory challenges and tasks [4]. It is plausible that there will be considerable variability in perceived availability across participants within a laboratory study; for example, if it is not clear how long the session will last or whether they will be allowed to smoke within a certain time-frame.…”
Section: Will Peak Provoked Craving Prove Superior To Cue-reactivity?mentioning
confidence: 99%
“…Ferguson & Shiffman, 2009), with smoking related cues being associated with increases in both craving (e.g. Schlagintweit, Good, & Barrett, 2014;Shiffman et al, 2012;Tong, Bovbjerg, & Erblich, 2007) and cardiac responses (e.g. Garcia-Rodriguez, Weidberg, Gutiérrez-Maldonado, & Secades-Villa, 2013;Jenks & Higgs, 2011) as well as with relapse to smoking among those attempting to quit smoking (Cox, Tiffany, & Christen, 2001;Ferguson & Shiffman, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…intercept, speed change rate). Many prior studies assessed smoking topography [29][30][31] , including videotaping of a single cigarette 32 . However, our study is the first to explore the utility of smoking topography in assessing nicotine dependence with an advanced modeling approach.…”
Section: Discussionmentioning
confidence: 99%